Compliance relationship analysis between environmental governance attention and environmental quality in the Beijing–Tianjin–Hebei region - Wang, Lin; Pan, Feng; Li, Xiaojing (Frontiers in Environmental Science, 2023)
This study analyzes the changes and allocation characteristics of environmental governance attention in Beijing-Tianjin-Hebei region based on government work report from 2002 to 2020 and explores the compliance relationship between environmental governance attention and environmental quality. The results show that: The allocation of local government environmental governance attention has high consistency with that of the central government, and the overall environmental governance attention shows a fluctuating trend upward. There is a long-term stable co-integration relationship between environmental governance attention and environmental quality in the Beijing-Tianjin-Hebei region, as well as a two-way Granger causality relationship in the short term. The nonlinear infiuence of environmental governance attention on environmental quality in the Beijing-Hebei-Tianjin region can be described by the LSTR2 model. During 2004-2016, environmental governance attention often had nonlinear effects on environmental quality. Since 2016, there has been a stable linear relationship between environmental governance attention and environmental quality. Finally, some policy suggestions on improving the local performance evaluation system and establishing a collaborative environment system for the Beijing-Tianjin-Hebei region have been put forward for the government.